Pseudorapidity density of charged particles in p + Pb collisions at √sNN=5.02 TeV - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Krawutschke, Tobias; Kweon, MinJung; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; et al. (Physical review letters, 2013)
The charged-particle pseudorapidity density measured over four units of pseudorapidity in nonsingle-diffractive p+Pb collisions at a center-of-mass energy per nucleon pair √sNN=5.02 TeV is presented. The average value at midrapidity is measured to be 16.81±0.71 (syst), which corresponds to 2.14±0.17 (syst) per participating nucleon, calculated with the Glauber model. This is 16% lower than in nonsingle-diffractive pp collisions interpolated to the same collision energy and 84% higher than in d+Au collisions at √sNN=0.2 TeV. The measured pseudorapidity density in p+Pb collisions is compared to model predictions and provides new constraints on the description of particle production in high-energy nuclear collisions.
Im Titel steht "sNN" unter dem Wurzelsymbol
Im Titel ist "NN" in sNN tiefgestellt
The ALICE collaboration: B. Abelev, V. Angelov, O. Busch, P. Glässel, R. Grajcarek, N. Herrmann, J. Klein, T. Krawutschke, M.J. Kweon, D. Lohner, X.-G. Lu, A. Maire, J. Mercado-Pérez, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, J. Ulrich, S. Vallero, Wang, B. Windelband, A. Zimmermann und weitere 955
Gesehen am 30.04.2021